Pengembangan Sistem Informasi Manajemen Inkubator Bisnis Teknologi di Institut Teknologi Kalimantan berbasis Website menggunakan Metode Extreme Programming - Aditya, Andhika; Utomo, Muchammad Chandra Cahyo; Mujahidin, Syamsul (Jurusan Matematika dan Teknologi Informasi, 2023)
The Kalimantan Institute of Technology has several organizations, one of which is a technology business incubator (IBT). The technology business incubator at ITK does not yet have an information system that can disseminate information regarding registration, selection and training information. IBT ITK requires media to be able to fulfill the need for information publication related to technology business incubators in ITK. Based on the previous problems, it is necessary to build a website-based management information system to facilitate the dissemination of information. The management information system that was built requires a systematic and structured method for its development, so the Extreme Programming method is used with the Laravel framework and MySQL as the database. The Extreme Programming method consists of several stages, namely observation, planning, iteration initialization, design, implementation (unit testing, code, refactor), system testing, retrospective. The results of the research show that the Extreme Programming method is capable of producing an information system that can meet the needs of stakeholders as shown from the test results.